MENELISIK PERSEPSI PERILAKU MILENIAL PENGGUNA INSTAGRAM DI ERA NEW NORMAL - Periantini, Ni Putu Novia; Darma, Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.12.TAHUN.2021, 2021)
This study aims to determine the perception of millennial behavior of Instagram users in the new normal era related to the implementation of customer path 5A. Consumer behavior has changed as a result of the new normal era. The application of customer path 5A can be seen from the millennial behavior of Instagram users starting from the Aware, Appeal, Ask, Act, and Advocate stages. The brand provider company must be a mentor throughout the customer stages from the Aware or awareness stage to the Advocate or endorsement stage. Business actors really hope that there will be an Act and Advocate process for products offered to consumers during this new normal era. This study uses a qualitative approach to dig deeper into the millennial behavior of Instagram users through customer path 5A. Data was collected through in-depth interviews with 10 millennial female informants with an age range of 18-24 years who are followers of the Instagram account @wimy_store. This study indicates that not all informants go through every stage of the 5A customer path starting from the Aware, Appeal, Ask, Act and Advocate stages. 2 Informants only went through the Aware, Appeal, and Ask stages, Act or purchase actions were not carried out due to considerations of the Covid-19 pandemic so that they paid more attention to needs, Advocate was not carried out because there had never been an Act before.